2003
DOI: 10.1038/sj.jp.7210905
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Opioid Analgesia and Neonatal Respiratory Depression

Abstract: , FRCP(C), FRCP(I) MDEpidural opioid analgesia is commonly employed as a therapeutic modality in the management of pain during labor. The general perception among health-care providers is that administered drugs remain in the maternal epidural space and do not compromise the respiratory status of newborns. We describe the clinical course of two newborns who developed respiratory depression following epidural fentanyl analgesia requiring administration of naloxone. The article further reviews the maternal-fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Withdrawal symptoms (e.g., irritability, hyperreflexia, hyperactivity, tremors, diaphoresis, tachypnea) and respiratory depression have been observed in neonates whose mothers were receiving fentanyl during pregnancy or labor (epidural route). 41 There are insufficient data to establish safety during breastfeeding; thus, caution is advised.…”
Section: Role Of Fentanyl In Cancer Pain 949mentioning
confidence: 99%
“…Withdrawal symptoms (e.g., irritability, hyperreflexia, hyperactivity, tremors, diaphoresis, tachypnea) and respiratory depression have been observed in neonates whose mothers were receiving fentanyl during pregnancy or labor (epidural route). 41 There are insufficient data to establish safety during breastfeeding; thus, caution is advised.…”
Section: Role Of Fentanyl In Cancer Pain 949mentioning
confidence: 99%
“…Despite this fact, later consequences of opioid use during labor were present. Babies delivered after their mothers received N300 μg fentanyl during the last 4 h of labor may be at greater risk of respiratory depression (Kumar and Paes, 2003). Moreover, infants whose mothers received 80 μg sufentanil show mild neurobehavioral depression (Capogna et al, 1989).…”
Section: Opioid Exposure During Labor In Human Studiesmentioning
confidence: 99%
“…15,30 Kumar (2003), identified newborn respiratory depression following maternal epidural analgesia combined with opioids and concluded that these neonates were more prone to respiratory sequelae in-utero and after birth. 31,32 The same author reported that epidural opioids diffused freely from the epidural space into the maternal blood, crossed the placental barrier and impacted on the fetal and newborn immature central nervous system (CNS), resulting in slightly higher opioid concentrations deposited in fetal peripheral tissue. 31 Increasing incidence of birth trauma Birth trauma experienced by the mother or the baby significantly influences the first and early breastfeeds.…”
Section: Continuous Monitoring Of Labourmentioning
confidence: 97%
“…31,32 The same author reported that epidural opioids diffused freely from the epidural space into the maternal blood, crossed the placental barrier and impacted on the fetal and newborn immature central nervous system (CNS), resulting in slightly higher opioid concentrations deposited in fetal peripheral tissue. 31 Increasing incidence of birth trauma Birth trauma experienced by the mother or the baby significantly influences the first and early breastfeeds. Birth trauma is defined as a physical or psychological event involving ''actual or threatened serious injury or death to the mother or her baby'' during the maternity phase.…”
Section: Continuous Monitoring Of Labourmentioning
confidence: 97%